The Obstacles Faced by PGSD International Students 2019 in Using English as Medium of Instruction - Meli Aslina; An Fauzia Rozani Syafei (Journal of English Language Teaching, 2022)
This study aims to find out the listening, speaking, reading, and writing obstacles faced by PGSD international class students 2019 in using English as a medium of instruction. Data was collected from 21 international class PGSD students in the 2019 entry year at Universitas Negeri Padang. In collecting data, the students were asked to fill out a questionnaire consisting of 41 questionnaire for 55 minutes. The results showed that these students had many obstacles in listening, speaking, reading, and writing. In other words, students are classified as having obstacles in using English as medium of instruction. In this case, the lecturers were asked to pay more attention to the student learning process such as often listening to western music, trying to talk to each other between students, reading texts, and writing things down about English texts.